Functional and Structural Analysis Reveals Distinct Biological Roles of Plant Synaptotagmins in Response to Environmental Stress. - García-Hernández, Selene; Rubio-Valverde, Lourdes; Rivera Moreno, María; Pérez-Sancho, Jessica; Morello-López, Jorge; Esteban del Valle, Alicia; Benítez-Fuente, Francisco; Beuzón-López, Carmen del Rosario; Macho, Alberto P.; Ruiz-López, Noemí; Albert, Armando; Botella-Mesa, Miguel Ángel (Wiley, 2024)
Endoplasmic reticulum–plasma membrane contact sites (ER–PM CSs) are evolutionarily conserved membrane domains found in all eukaryotes, where the ER closely interfaces with the PM. This short distance is achieved in plants through the action of tether proteins such as synaptotagmins (SYTs). Arabidopsis comprises five SYT members (SYT1–SYT5), but whether they possess overlapping or distinct biological functions remains elusive. SYT1, the best‐characterized member, plays an essential role in the resistance to abiotic stress. This study reveals that the functionally redundant SYT1 and SYT3 genes, but not SYT5, are involved in salt and cold stress resistance. We also show that, unlike SYT5, SYT1 and SYT3 are not required for Pseudomonas syringae resistance. Since SYT1 and SYT5 interact in vivo via their SMP domains, the distinct functions of these proteins cannot be caused by differences in their localization. Interestingly, structural phylogenetic analysis indicates that the SYT1 and SYT5 clades emerged early in the evolution of land plants. We also show that the SYT1 and SYT5 clades exhibit different structural features in their SMP and Ca2+ binding of their C2 domains, rationalizing their distinct biological role.
Keywords: Estrés (Fisiología); Plantas - Efectos del estrés; Fisiología vegetal; Arabidopsis - Efectos del estrés; Arabidopsis; Abiotic stress; Biotic stress; C2 domain; Contact sites; SMP domain; Synaptotagmins